جهود الشّيخ عبد الكريم المُدرِّس في التفسير وعلوم القرآن - باحو, محمد العيد (University of eloued جامعة الوادي, 2021)
" إن بين طرفي هذا البحث دراسة تهدف إلى إبراز جهد من جهود علماء أمتنا في العصر الحديث ألا وهو الشيخ عبد الكريم المُدرِّس كنموذج، وذلك من خلال: - ترجمة للشيخ للوقوف على شيء من جوانب حياته الشخصية والاقتصادية والعلمية، لتتجلى لنا التحديات التي واجهها علماؤنا الأفاضل في سبيل الدعوة إلى الله ونشر العلم تدريسا وتأليفا. - إبراز جهود الشيخ في التفسير وعلوم القرآن والتطرق إلى قضايا كل منهما مما هو متعارف عليه في هذا الفن كون الشيخ مفسرا وله تفسير مشهور. وقد خلُصت الدراسة في هذا البحث بنتائج من شأنها أن تبين شيء ملامح التجديد عند مفسري العصر الحديث وطرائقهم في التفسير لاستنباط وإسقاط النصوص الشرعية على واقعنا المعاصر. "Among the path of this research is a study that aims to highlight one of the efforts of our nations scholars in the modern era، namely sheikh Abdul karim al-mudarres, may God have mercy on him، as a model. This is through: - A translation of the sheikh to find out everything from the aspects of his personal، economic and practical life، in order to show us the updates that our distinguished scholars faced in the path of calling to God and spreading knowledge in teaching and authorship. - Highlighting the efforts of the sheikh in the interpretation and sciences of the Quran and addressing the issues of each accused of what is customary in this art because the sheikh is an interpreter and has a well-known interpretation. The study concluded in this research with results that would show something of the features of renewal about modern interpreters and their methods of interpretation to derive legal texts on our contemporary reality. "
علوم قرآن
Keywords: جهود، التفسير المعاصر، ملامح التجديد; Efforts, interprétation contemporaine, traits de renouveau